Association between Child Diarrhea and Maternal Depression - Milad, Grace; Izzeldin, Saria; Tofail, Fahmida; Ahmed, Tahmeed; Hakim, Maliha; Khalil, Ibrahim; Petri, William A (Journal of Shaheed Suhrawardy Medical College, 2013)
CORRECTION: The following authors were added to this paper on 11/10/2013: Grace Milad; Saria Izzeldin; Tahmeed Ahmed; William A. Petri. The author Mohammad Ibrahim Khalil was changed to Ibrahim Khalil Background: Maternal depression has been found to be associated with increased diarrheal incidence and childhood malnutrition. Objective: The purpose of the present study was to observe whether the Self- Reporting Qustinative (SRQ-20) questionnaire was sensitive enough to pick-up the depressive symptoms of mothers in the urban slum community. Methodology: This was a pilot study in a Dhaka Shantytown and women were interviewed to examine the relationship between maternal depression and their children's diarrheal morbidity. In addition to other socio-demographic information, the Self-Reporting Questionnaire (SRQ-20) was used to screen for maternal depression. Result: A total number of 55 women were interviewed to examine fifty-one percent of mothers scored within the high-risk psycho-morbidity group, suggesting depression. High SRQ scores significantly correlated with poor marital relationships (Regression coefficient ± standard error =-0.624+0.225, p=0.008; 95%CI:-1.076, -0.172). High-risk mothers breastfed for a shorter duration than low-risk mothers (3.4 vs. 4.4 months, p=0.35) and their children had more diarrheal episodes (2 episodes vs. 1, p=0.18), although these differences did not show statistical significance. Conclusion: Depression is common among mothers in urban slums and that a well-designed large study is required to further explore the provocative relationship between maternal depression and child diarrhea with subsequent malnutrition to improve the quality of life of those at risk. DOI: http://dx.doi.org/10.3329/jssmc.v5i1.16199 J Shaheed Suhrawardy Med Coll, 2013;5(1):14-20